'Awkward Antarctic nationalism': bodies, ice cores and gateways in and beyond Australian Antarctic Territory/East Antarctica. (11th October 2016) - Dodds, Klaus
ABSTRACT: This paper explores 'awkward Antarctic nationalism' and builds on the critical scholarship that explores the contours and contradictions of everyday, mundane, banal and even hot polar nationalisms. The emphasis on 'awkward' is designed to draw attention to the resonances and affordances that are associated with Australian polar nationalism in and beyond the Australian Antarctic Territory/East Antarctica. Using the 2016 Australian Antarctic strategy: 20 year action plan as a starting point, it considers how bodies, ice cores and gateways are put to work in order to address a fundamental pressure facing all claimant states. That is how to reassure domestic audiences that claims to territory and access are safe, sovereign and secure without alienating others with whom one wishes to do business within a particular area of Antarctica. More broadly, the paper concludes that both claimant states and non-claimant states are rubbing up against one another in areas such as custodianship, environmental stewardship and polar science and logistics. This has implications for how we interrogate the ideals and practices of the Antarctic Treaty.